A construção de vínculos afetivos entre professores de matemática e seus alunos: um estudo em uma instituição confessional - Silva, Antonio Carlos Martins da (2024)
The study started from the interest in understanding the perception of teachers regarding the affectivity and the teaching-learning of mathematics, how they understood the importance of bonds built between the teacher and the student, in the confessional context. The survey was carried out at a private confessional school in the city of São Paulo, the subjects of the survey were four teachers of the institution who teach the final years of elementary school, the survey was carried out with the population. The theoretical basis was the Pillars of the Salesian Education by Scaramussa (1993), the affectivity of Wallon (2017) and the learning of mathematics and the affectivity of Chacón (2003). The data collection was held by means of a form from Forms for the profile analysis and the model of semi-structured interviews. The answers were categorized and the analysis was based on these data. The results showed that the teachers understand that the affectivity is fundamental to the teaching-learning process, as well as the creation of affective bonds are necessary for any pedagogical strategy applied in the classroom. Finally, the proposal is to present the results of the survey to the subjects and stimulate reflexions on the topic